Encyclopedia of Ukraine. Volume 5, St-Z - Struk, Danylo Husar, 1940-1999 (Toronto : University of Toronto Press, 1993)
Over thirty years in the making, the most comprehensive work in English on Ukraine is now complete: its history, people, geography, economy, and cultural heritage, both in Ukraine and in the diaspora.
Translation of: Ent͡syklopedii͡a ukraïnoznavstva.
Includes bibliographical references.
PDF (JSTOR, viewed July 16, 2015).
JSTOR
Keywords: Ukraine -- Encyclopedias; HISTORY -- Europe -- Eastern; HISTORY -- Europe -- Former Soviet Republics; HISTORY -- Europe -- Russia & the Former Soviet Union; Ukraine; Encyclopedias